2021
DOI: 10.3892/ijmm.2021.4887
|View full text |Cite|
|
Sign up to set email alerts
|

Long non‑coding RNA KCNQ1OT1 promotes nasopharyngeal carcinoma cell cisplatin resistance via the miR‑454/USP47 axis

Abstract: Long non-coding RNAs serve an essential role in drug resistance in various types of cancer, including lung, breast and bladder cancer. The present study aimed to investigate whether KCNQ1 opposite strand/antisense transcript 1 (KCNQ1OT1) was associated with cisplatin (DDP) resistance in nasopharyngeal carcinoma (NPC). KCNQ1OT1, microRNA (miR)-454 and ubiquitin specific peptidase 47 (USP47) expression levels were measured via reverse transcription-quantitative PCR. 5-8F/DDP and SUNE-1/DDP cell viability and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…More recently, many other lncRNAs have been associated with NPC progression, with their capacity of sponging different microRNAs [ 58 , 61 , 62 , 63 , 71 , 72 , 73 , 74 ]. Additionally, in NPC patients, a large number of lncRNAs were also associated with cisplatin resistance [ 42 , 43 , 44 , 45 , 75 , 76 , 77 , 78 ] and radioresistance [ 54 , 79 , 80 ].…”
Section: Lncrnas In Rare Tumorsmentioning
confidence: 99%
“…More recently, many other lncRNAs have been associated with NPC progression, with their capacity of sponging different microRNAs [ 58 , 61 , 62 , 63 , 71 , 72 , 73 , 74 ]. Additionally, in NPC patients, a large number of lncRNAs were also associated with cisplatin resistance [ 42 , 43 , 44 , 45 , 75 , 76 , 77 , 78 ] and radioresistance [ 54 , 79 , 80 ].…”
Section: Lncrnas In Rare Tumorsmentioning
confidence: 99%
“… 99 Existing research results indicated that KcNQ1OT1 enhanced DDP resistance in NPC cells via the miR‑454/USP47 axis, suggesting a potential therapeutic target for patients with DDP‑resistant NPC. 100 Wang et al demonstrated elevated expression levels of lncRNA SLC25A21-AS1 in NPC tissues and cells. In addition, high expression of SLC25A21-AS1 could target miR-324-3p and thus mediate IL-6, resulting in enhanced proliferation and multidrug resistance in NPC cells.…”
Section: Non-coding Rnas Involved In Drug Resistance Of Npcmentioning
confidence: 99%
“…Therefore, KcNQ1OT1 might serve as a potential target for overcoming DDP resistance in NPC chemotherapy. 100 Wang et al showed that miR-181a could enhance the sensitivity of nasopharyngeal carcinoma cells to paclitaxel by promoting apoptosis, while in nasopharyngeal carcinoma, lncCCAT1 could directly bind to miR-181a, thus inhibiting the biological function of miR-181a and making nasopharyngeal carcinoma cells less sensitive to paclitaxel. 105 In addition, lnc SLC25A21-AS1 regulates IL-6 by targeting miR-324-3p, making nasopharyngeal carcinoma resistant to multiple chemotherapeutic agents.…”
Section: Non-coding Rnas Involved In Drug Resistance Of Npcmentioning
confidence: 99%
“…With the gradual application of molecular technology to the diagnosis and prognostic treatment of diseases, long noncoding RNAs (ln-cRNAs) have developed into a new biomarker and therapeutic target for a variety of human diseases. LncRNAs are over 200 in length and have no protein coding ability, which are important regulatory factors involved in transcription, differentiation, invasion, apoptosis and other biological processes [13,14]. In existing studies, Thomas et al proved Silencing LncRNA PVT1 Reverses High Glucose-Induced Regulation of the High Expression of PVT1 in HRMECs by Targeting miR-128-3p…”
Section: Introductionmentioning
confidence: 99%